2020
DOI: 10.1021/acs.jafc.0c03738
|View full text |Cite
|
Sign up to set email alerts
|

Coupling 16S rDNA Sequencing and Untargeted Mass Spectrometry for Milk Microbial Composition and Metabolites from Dairy Cows with Clinical and Subclinical Mastitis

Abstract: The internal environment of the cow's udder directly affects the udder health and milk quality. 16S rDNA sequencing and liquid chromatography−mass spectrometry (LC−MS) methods were used to investigate the significant differences in milk microbial diversity and metabolites among cows that are healthy (H) and those suffering from subclinical mastitis (SM) and clinical mastitis (CM). Results uncovered more than 16 and 192 differently abundant microbiota at the phylum and genus levels, respectively, and 673 differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 43 publications
2
18
2
Order By: Relevance
“…Serum metabolome of the same cows with/without mastitis was observed in parallel, granting a multifaceted observation of the underlying mechanisms relating cows' metabolome to mastitis. A potential limit of the work could be represented by the limited number of samples analyzed, even if such number is in line with previous works devoted to the evaluation of the consequences of mastitis on milk metabolome [22,26]. In this respect, it is worth noticing that, despite the large inter-variability among samples evidenced in Figure 2, none of the samples could be considered as an outlier.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Serum metabolome of the same cows with/without mastitis was observed in parallel, granting a multifaceted observation of the underlying mechanisms relating cows' metabolome to mastitis. A potential limit of the work could be represented by the limited number of samples analyzed, even if such number is in line with previous works devoted to the evaluation of the consequences of mastitis on milk metabolome [22,26]. In this respect, it is worth noticing that, despite the large inter-variability among samples evidenced in Figure 2, none of the samples could be considered as an outlier.…”
Section: Discussionmentioning
confidence: 61%
“…As one of the most economically important diseases in the dairy production industry, bovine mastitis has been studied from a variety of perspectives, such as milk yield and composition [22], milk bacterial communities [23] and milk metabolome [24]. In terms of milk metabolome, there are no complete reports containing quantitative information for each metabolite that can be identified by 1 H-NMR.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated amino acid metabolism in the rumen of cows with SCM fed inulin might be attributed to the degradation of increased rumen microbial protein. The thiamine metabolic pathway was also previously observed to be inhibited in the feces and milk of dairy cows with mastitis ( 7 , 44 ). As a cofactor for many biochemical reactions, vitamin B might participate in the inhibition of inflammation ( 7 ).…”
Section: Discussionmentioning
confidence: 77%
“…Psychrophilic bacteria of the genus Pseudomonas have been found to cause milk spoilage. However, the Pseudomonas bacterium is not unique in healthy milk; it is also the only bacteria that exhibits a random distribution in milk microorganisms and is usually inhibited by the probiotic network in healthy milk cows [ 52 , 53 ]. However, Pseudomonas which was significantly enriched in colostrum of cows housed on the peanut–rice combination, as a potential pathogen, is still worth noting as a risk factor for udder health.…”
Section: Discussionmentioning
confidence: 99%
“…Akkermansia , belonging to the phylum Verrucomicrobial , is considered to be a beneficial microorganism and is negatively related to certain metabolic disorders [ 55 ]. Alistipe of the phylum Bacteroides is not present in abundance in milk with mastitis compared with healthy milk [ 52 ]. Derakhshan [ 50 ], and Doyle et al [ 56 ], reported that Ruminococcaceae , as the dominant flora in colostrum, is easily affected by the environment.…”
Section: Discussionmentioning
confidence: 99%